Rancang Bangun Aplikasi Administrasi Rawat Jalan Pada Kliniki Geo Medika - Yamanta, Ongky Anjar; Amelia, Tan; Wulandari, Sri Hariani Eko (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
Primary health care provided by the Geo Medical Clinic is an outpatient practice General Practitioners and Physician Specialist. With outpatient practice as primary health care, the administration of outpatient become an important function in the process. The existing problems in the system of outpatient administration is currently in the registration process still found the quest difficulty to lose the medical records of patients who have an impact on delays in the registration process, the data redundancy, and fault diagnosis of the doctor. The doctor activity that brings patient records to the cashier to make the process of further examination of patients can not be directly performed. It certainly could have an impact on the loss of medical records and patient does not perform the payment process. Of the problem analysis found that the use of the card in the manufacture of patient data and medical records, and not integrated administrative system there is a major problem in the practice of outpatient clinic services Medika Geo. Those problems can be overcome with the integrated applications ranging from registration until the payment. This application can assist in the registration process until the payment process, as it can help in recording patient data and medical records and can reduce registration queues and help doctors to consider the track record of the patient at the outpatient medical record so as to produce an accurate and easy. To process payments become computerized and integrated in order to prevent loss of data and medical records of patients and assist in making clinical report